Transfer and treatment of personal data in the criminal process. Progress and immediate challenges of the directive (EU) 2016/680 - Mª Isabel González Cano (Revista Brasileira de Direito Processual Penal)
Collection, transfer and processing of personal data, as a means of investigation and obtaining incriminating material regarding the owner of such data, involve measures that affect a fundamental right, the right to the protection of personal data. This being the case, the legitimate interference of the competent authorities for the purposes of repression, investigation and criminal prosecution, must conform to the guarantee standards and the guiding principles of any investigation measure that affects fundamental rights, both to legitimize such measure and to Obtaining evidence of legal charge or incrimination. Thus, the collection, collection and processing of personal data, through the relevant investigation measures, shall be governed by the principles of specialty, suitability, exceptionality, necessity and proportionality of said measures, to be weighed by the judicial authority authorizing them, in accordance with art. 588 bis a. of the Law of Criminal Procedure.